PENDAMPINGAN PENGOLAHAN KECAP BERBAHAN DASAR DAGING ITIK DI KELOMPOK WANITA TANI NUSA INDAH KELURAHAN SUNGAI TIUNG KECAMATAN CEMPAKA BANJARBARU - Dharmawati, Siti; Gunawan, Aam; Sugiarti, Sugiarti (Universitas Mataram, 2025)
This Community Service Program aims to empower women farmer groups to diversify and increase the economic value of duck meat in the form of processed duck soy sauce products. The background of this activity is to realise one of the Banjarbaru City Government programs, namely urban farming, one of which is utilising products from poultry livestock, namely ducks. The target of this activity was the Nusa Indah women farming group in Sungai Tiung Village, Banjarbaru City, South Kalimantan, attended by 22 participants. The problems faced by the group are diversification of products from duck meat, product quality, and SNI. The methods used in this activity are technical guidance, counselling, and direct practice in processing duck meat-based soy sauce. The results of the activity were that participants arrived on time (100% of participants arrived at the planned time), participants were active in discussions and brainstorming 70–80%, and active in processing soy sauce 85%. Based on the results of the assessment using a questionnaire, 68.19%-100% of participants understood the material, 27.27% of participants had a strong desire to develop products and market products, 45.45% tried to market products, and 27.27% had no desire to develop products. . The participants' assessment of the soy sauce produced using organoleptic tests in the form of colour, aroma, and taste stated that the colour was blackish brown (81.82%), the fragrant aroma typical of soy sauce was 81.82%, and the delicious taste was typical of soy sauce (72.27%). In general, community service activities in the Nusa Indah Women's Farmers Group were successful, with indicators of participant involvement > 90% and participants' ability to apply the technology presented > 70%.